Women and the colonial state : essays on gender and modernity in the Netherlands Indies, 1900-1942 - Locher-Scholten, Elsbeth, 1944- (Amsterdam University Press, 2000)
"This book deals with the ambiguous relationship between Indonesian and European women and the colonial state in the former Netherlands Indies (or Dutch East Indies) between 1900 and 1942. How did women of different racial backgrounds relate to each other and to 'the colonial project'? How did the colonial state address women's issues? What were the constructions of gender which dominated the discourse on these issues?" "The content is based on new data from a variety of sources, such as censuses, colonial archives, rural labour reports, household manuals, children's fiction and Indonesian press surveys. An introductory essay combines the outcomes of the case studies and relates those to ongoing debates within the history of colonialism. The book thus provides the reader with new insights in the social dynamics of colonial society and politics in relation to gender."--Jacket